Multimorbidity at sea level and high-altitude urban and rural settings: The CRONICAS Cohort Study. (5th November 2019) - Miranda, J Jaime; Bernabe-Ortiz, Antonio; Gilman, Robert H; Smeeth, Liam; Malaga, German; Wise, Robert A; Checkley, William; ,
Objective: To characterize the prevalence and clustering of multimorbidity in four diverse geographical settings in Peru. Methods: Multimorbidity, defined as having ≥2 chronic conditions, was studied in adults aged ≥35 years in four diverse settings in Peru: Lima, Tumbes, and urban and rural Puno. Six of these conditions (alcohol disorder, asthma, chronic obstructive pulmonary disease, depression, diabetes, and hypertension) were cataloged as objectively ascertained chronic conditions and paired in dyads to explore clusters of multimorbidity. Results: We analyzed data from 2890 adults, mean age 55.2 years, 49% males. Overall, 19.1% of participants had multimorbidity, ranging from 14.7% in semi-urban Tumbes to 22.8% in Lima. The dyads with the highest coexistence (approximately 20%) were observed in hypertension and diabetes in Tumbes, whereas the dyads with lowest coexistence (approximately 1%) were those involving asthma in all study sites. In terms of clusters, Tumbes showed a predominance of hypertension and diabetes, urban and rural Puno a predominance of depression and alcohol disorders, and Lima a higher degree of coexistence of all of the six conditions than in the other clusters. Conclusion: Multimorbidity is common and the pattern of clusters is highly heterogeneous. The conditions to prioritize will vary in each setting.